Pengembangan Kapabilitas Web Desa Apuan Sebagai Wadah Promosi Wisata Desa Apuan - Wardani, Kadek Devi Kalfika Anggria; Dewi, Gusti Ayu Made Indrayani; Gorda, Anak Agung Ngurah Eddy Supriyadinata; Anak Agung Ngurah Oka Suryadinatha Gorda (Ilin Institute, 2023)
The development of information technology grows and develops in the midst of community activities because it can be used to support branding activities. Every village nowadays must have a village website. Apuan Village is located in Susut sub-district, Bangli district which has natural tourism potential in the form of waterfalls and spiritual tourism which are still rarely exposed, especially on the village's website. The results of field observations and monitoring of the village website show that currently the use of the website in Apuan Village is only limited to providing information about activities that have been carried out in Apuan Village, while village potential is not published on the website. The purpose of this service activity is to assist in developing the capabilities of the Apuan Village website as a forum for tourism promotion. The method in this service activity uses observation, implementation, monitoring and evaluation methods. This activity achieved the previously stated goals of increasing the number of visits to the Apuan Village website by 30% and the number of readers of publications regarding tourist destinations in Apuan Village also increased. This means that service activities in increasing the capability of the village website have a positive and expected impact on village officials along with public relations and all levels of society in Apuan Village.